Islamic Religious Education Learning Methods - Moch. Salman Alfarizi; Sunarto (STIT Attaqwa, 2024)
Problems that are often experienced in the learning process include learning difficulties, varying levels of creativity between teachers and students, inappropriate application of teaching methods, limitations in the use of learning media. This research aims to investigate and analyze religious learning methods that fall into categories centered on students studying Islamic religious education. This research uses the library research research method, by taking a descriptive-analytical approach with this type of literature review. The results of this research are that Islamic religious learning methods that are student-centered, including the Inquiry-Based Learning (IBL) Method, promote students' critical and analytical thinking skills in finding answers to the problems they face. The Group Discussion Method, with an interactive approach, is able to increase students' enthusiasm for learning through sharing ideas and debating relevant topics. Practice Methods provide opportunities for students to conduct experiments and real practice, helping them find answers to problems through hands-on experience. The Active Learning method encourages students to think critically and creatively, contextualizing learning materials with everyday life situations. The Peer Tutor method utilizes the role of peers as tutors, increasing understanding through closer communication and interaction. Overall, these methods, with their various innovations, have proven effective in improving the quality of Islamic religious learning, helping students develop critical thinking skills, problem solving, and a deeper understanding of Islamic teachings.